Power representation in the leadership of academic libraries in Indonesia - Laugu, Nurdin (Berkala Ilmu Perpustakaan dan Informasi, 2021)
Introduction. Libraries as a dynamic environment have supported dynamic interactions in various aspects of life. These interactions occur in several frames such as culture, social, and ideology that pose power in library leadership at universities. Data Collection Method. In-depth interviews with nine informants, consisting of heads, librarians, and library staff in three libraries, conducted unstructurally between 2018 and 2020. Interview data was used as the main data collection technique, supported by observations and documentation. Data Analysis. Miles and Huberman's model with three stages, i.e. data reduction, data presentation, and conclusion or verification, was employed to interpret findings. Results and Discussion. The results showed five main issues, which are directly related to power representation in libraries. These issues include religious understanding, institutional vision, temporary power, seniority of library personnels, and the influence of the library collection development. Conclusion. The representation of power in library leadership practices has emerged in the frames of religiosity, organizational ideology, seniority, power, and impact of library collection. Therefore, this research contributes to library science theorists and practitioners concerning the awareness of the power representation issues.